The Management of Inflatable Penile Prosthesis Erosion and Infection following Iatrogenic Aspiration - Ali Baydoun; Alexander Benben; Matthew Skalak; Jordan Bilbrew; Mazen Abdelhady (Case Reports in Urology)
This case report presents a unique and previously unreported case of malfunction, infection, and erosion of an inflatable penile prosthesis (IPP) resulting from iatrogenic injury during a priapism aspiration procedure performed by an emergency medicine physician. The patient, a 75-year-old male with a history of IPP placement for erectile dysfunction, presented with urinary retention and priapism, leading to inadvertent deflation of the IPP during aspiration. Subsequent evaluation revealed a pinhole opening on the scrotum, indicating infection and erosion of the prosthesis tubing. The patient underwent emergent explantation of the infected IPP, washout, cystoscopy, and insertion of a suprapubic tube. Intraoperative cultures identified Escherichia cloacae as the causative pathogen. This case highlights the importance of thorough chart review to identify patients with IPPs before aspiration procedures and emphasizes the need for healthcare provider education regarding potential complications in this patient population. Early recognition and management of such complications are crucial for optimal patient outcomes. While IPP placement remains a highly satisfactory treatment for erectile dysfunction, this case highlights the importance of vigilance to ensure the best care for patients with penile prostheses. It is noteworthy that ultimately, a new IPP was not placed in this patient due to the patient’s significant medical comorbidities.